Minocycline inhibits hyperpolarization-activated currents in rat substantia gelatinosa neurons. (August 2015) - Liu, Nana; Zhang, Daying; Zhu, Mengye; Luo, Shiwen; Liu, Tao
Abstract: Minocycline is a widely used glial activation inhibitor that could suppress pain-related behaviors in a number of different pain animal models, yet, its analgesic mechanisms are not fully understood. Hyperpolarization-activated cation channel-induced I h current plays an important role in neuronal excitability and pathological pain. In this study, we investigated the possible effect of minocycline on I h of substantia gelatinosa neuron in superficial spinal dorsal horn by using whole-cell patch-clamp recording. We found that extracellular minocycline rapidly decreases I h amplitude in a reversible and concentration-dependent manner (IC50 = 41 μM). By contrast, intracellular minocycline had no effect. Minocycline-induced inhibition of I h was not affected by Na + channel blocker tetrodotoxin, glutamate-receptor antagonists (CNQX and D-APV), GABAA receptor antagonist (bicuculine methiodide), or glycine receptor antagonist (strychnine). Minocycline also caused a negative shift in the activation curve of I h, but did not alter the reversal potential. Moreover, minocycline slowed down the inter-spike depolarizing slope and produced a robust decrease in the rate of action potential firing. Together, these results illustrate a novel cellular mechanism underlying minocycline's analgesic effect by inhibiting I h currents of spinal dorsal horn neurons. Highlights: Hyperpolarization-activated cation currents ( I h) are inhibited by minocycline. Minocycline inhibits I h by binding to the extracellular site of hyperpolarization-activated cyclic nucleotide-gated channels. Minocycline negatively shifts the activation curve of I h but do not alter the reversal potential. Minocycline decrease spiking rate by slowing down the inter-spike depolarizing slope.